Habitat Design: New Directives. (2016) - Khan, Asif R.
Abstract: For a city in transition not only is there a need for planners to provide accountability of development and growth continuum but also ensure a pattern for objective spatial description network. Orientation towards ideal cognition and provision of a framework for accountability is vital. Interpretation of the structure of mould forming the physical environment made up of people and space with time playing an integral contextually relevant catalyst is essential to evolve experiential knowledge about the urban stature. The planned or self evolved urban grammar owing a perceptual sense of order with accountability for continuum could often be treated as the base order with perpetual indicators defining the edges of physical realm associated with a developing conurbation. The study provides insight into new urbanisation trends prevailing in India and approaches propagated by individuals, organisations and statutory bodies for realizing a better built habitat. A theoretical ideation: Critical Proposition Theory, a decisive framework to ensure progress in the right direction has been derived, supported by graphical - visual illustrations with cognitive reasoning. It is apparently evident, how these cities are envisioned with time would determine the practicability of subsistence for future generations.